Activity of ABCG2 Is Regulated by Its Expression and Localization in DHT and Cyclopamine‐Treated Breast Cancer Cells. Issue 10 (7th April 2016) - Chua, Vivian Y.L.; Larma, Irma; Harvey, Jennet; Thomas, Marc A.; Bentel, Jacqueline M.
ABSTRACT: Elevated expression of the efflux transporter, ATP‐binding cassette subfamily G isoform 2 (ABCG2) on the plasma membrane of cancer cells contributes to the development of drug resistance and is a key characteristic of cancer stem cells. In this study, gene expression analysis identified that treatment of the MCF‐7 and T‐47D breast cancer cell lines with the androgen, 5α‐dihydrotestosterone (DHT), and the Hedgehog signaling inhibitor, cyclopamine downregulated ABCG2 mRNA levels. In MCF‐7 cells, and in Hoechst 33342 lo /CD44 hi /CD24 lo breast cancer stem‐like cells isolated from MCF‐7 cultures, ABCG2 was accumulated in cell‐to‐cell junction complexes and in large cytoplasmic aggresome‐like vesicles. DHT treatments, which decreased cellular ABCG2 protein levels, led to diminished ABCG2 localization in both cell‐to‐cell junction complexes and in cytoplasmic vesicles. In contrast, cyclopamine, which did not alter ABCG2 protein levels, induced accumulation of ABCG2 in cytoplasmic vesicles, reducing its localization in cell‐to‐cell junction complexes. The reduced localization of ABCG2 at the plasma membrane of MCF‐7 cells was associated with decreased efflux of the ABCG2 substrate, mitoxantrone, and increased sensitivity of cyclopamine‐treated cultures to the cytotoxic effects of mitoxantrone. Together, these findings indicate that DHT and cyclopamine reduce ABCG2 activity in breast cancer cells by distinct mechanisms, providing evidence to advocate the adjunct use of analogous pharmaceutics to increase or prolong the efficacy of breast cancer treatments. J. Cell. Biochem. 117: 2249–2259, 2016. © 2016 Wiley Periodicals, Inc.